La vulneración del derecho constitucional a la libertad de expresión y su incidencia en el honor de las personas. - Anchundia Triviño, Jorge Washington (2017)
The project called The Vulneration of Constitutional Law to Freedom of Expression and its Impact on the Honor of the People, the approach of this reform is born from the fact that the media complain that the honor of people as individuals and as a whole . In most cases those who exercise a public function, in which they prevail of their power offend all those who oppose their actions and especially those who think differently, being the subject of insults or threats that cause a Moral damage, psychologically affecting the person and his family leaving an irreparable sequel. In the process of constructing our proposal, we applied surveys and interviews to people related to the problem, such as judges, lawyers in free exercise, employees in the judicial function and citizens who were affected in their honor. Through bibliographic research we analyze laws and doctrines of Latin American countries. Concluding that in Ecuador we do not have an authentic Freedom of Expression that guarantees the individual an absolute freedom to express what he feels and thinks. We consider that the current legal framework has shortcomings that must be corrected for the benefit of the community and this is achieved by constantly analyzing the changes that arise in a society where the loss of values and inappropriate use of technology impacts on human behavior.